Post‐mortem investigation into a death involving doping agents: The case of a body builder. Issue 10 (14th August 2022) - Favretto, Donata; Stocchero, Giulia; Pertile, Roberto; Stimamiglio, Raffaella; Cirnelli, Antonello; Galeazzi, Maddalena
Abstract: Introduction: A young male was found dead on the bed of a hotel room. He was expected to take part in a bodybuilding competition the day after. During the site inspection, drugs of different types were found. The next day, an autopsy was performed. The evidence of cardiomegaly with organ congestion involving lung, liver, kidneys, adrenal glands, spleen and brain was confirmed by both the autoptic and the histopathological exam. However, the cause of death needed to be investigated. Methods: A thorough toxicological investigation was undertaken by gas chromatography–mass spectrometry (GC‐MS), liquid chromatography‐high resolution mass spectrometry (LC‐HRMS) and liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) on samples of urine, blood and hair. Results and discussion: Clenbuterol, a long‐acting selective beta2 agonist, was found in both blood (1 ng/ml) and urine (1 ng/ml), and evidence of its use was provided by the analysis of the 3‐cm hair (25 pg/mg). The main metabolite of drostanolone (2 alpha‐methyl‐androsterone), an anabolic steroid, was found in the urine (202 ng/ml), where an increased ratio of testosterone/epitestosterone (T/E = 11) emerged. Due to the results of the hair analysis, a long‐term use of various anabolic steroids was supposed. The integrated analysis of the results and the absence of other possible causes (such as trauma or cardiac conduction anomalies) led to the identification of the abuse of doping substances as the underlying cause of death. Conclusion: Hair analysis has proven to be crucial in identifying drug misuse and the contributing cause of death.